Penatalaksanaan Fisioterapi Pada Kasus Bronkiektasis Di Balai Besar Kesehatan Masyarakat Surakarta - Serin, Listiyana, Dwi Kurniawati, SSt.FT.,M.Kes (2015)
Background: Bronchiectasis is a chronic disease characterized by progressive dilatation of the bronchi and bronchioles that is settling and thickening of the bronchial wall . This situation is caused by a viral or bacterial infection is chronic , and is followed by the release of inflammatory mediators. Purpose: Bronchiectasis include physiotherapy on short-term goals and long term goals . In the short-term goal is to reduce shortness of breath , pain , and improve thoracic expansion and long-term goal to restore functional activities. Method: modalities used in the form of case studies Infra red , nebulizer , and thoracic expansion exercise . Result: a decrease shortness of breath , pain and there has been no increase in thoracic expansion. Conclusion: So with the provision of physiotherapy modalities such as Infra red , Nebulizer , and Thoracic Expansion Exercise and the provision of education can reduce the problems on the condition Bronchiectasis shortness of breath, pain , and limitations ekspasni meningkatakn thoracic and functional activity .